Variation in Responses of Individual Farmers to Uniformity Program - Sudhiatiningsih, Ni Nyoman Sri Natih (UI Scholars Hub, 2014)
This manuscript describes the phenomenon of variation in farmers’ individual responses to the realization of “top-down” government policy implemented during regional autonomy. The study aims to understand the process of social change as well as other theoretical problems with attention to contextual factors of the emergence of such variations. Individuals are active agents in interpreting phenomena and make decisions. Using an ethnographic approach and progressive contextualization, I am able to describe the variation in responses of Kahuman village farmers, Polanharjo Subdistrict, Klaten Regency, when Inpari 13 Programme was carried out. During the growing season of Inpari 13 in 2011, Kahuman’s farmers responded differently to program admission process, realization of planting, and pest control through spraying. The emergence of the varied responses indicates that individual farmers still determine all decisions within each farm management practices that they do.